Batterer typologies: substance use, impulsivity and results of an IPVAW offender treatment program in Spain - Mateo-Fernández, Pedro V.; Osa-Subtil, Iria; Ronzón-Tirado, Román; de la Peña Fernández, María Elena (Frontiers in Psychiatry, 2025)
IntroductionBatterer impulsivity and substance use are relevant factors in the study of gender violence. Impulsivity is defined by the tendency to act suddenly and without forethought. Combined with drunkenness, it can materially increase the likelihood of intimate partner violence.MethodsThe present study examines substance use and impulsivity among a sample of 243 men convicted of IPVAW offences under the Spanish Gender Violence Act (Organic Law 1/2004) in relation to the levels of violence and psychopathologies presented by these perpetrators, in order to understand the results of court-ordered psychological treatments provided under Spain’s Gender Violence Offenders Intervention Program. The participants, aged an average 39.1 years, were classified into three types based on demographic factors, substance use and other relevant variables. Meanwhile, the tools used included AUDIT and EuropASI to assess alcohol consumption, CTS2 to measure the frequency and intensity of violent behaviors over the last year, and SCID-II for personality disorders.ResultsOur findings reflected marked improvements in conflict resolution strategies, especially in terms of reduced psychological violence and sexual coercion, but not physical violence. Impulsivity and early-onset alcohol use were identified as key risk factors for violent behavior. Latent class analysis revealed the existence of three sub-types, comprising high-risk batterers displaying high levels of aggression and drinking problems, low-risk batterers displaying high levels of secondary psychopathy, and medium-risk batterers.DiscussionThe study underscores the need for differentiated treatment approaches to address both psychological problems and substance use, while highlighting the need for personalized interventions to rein in violent behavior and prevent reoffending. We We propose a future longitudinal study to throw light on the subsequent developmental paths taken by IPVAW offenders.